Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1515/aoter-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Recuperator with microjet technology as a proposal for heat recovery from low-temperature sources

Abstract: A tendency to increase the importance of so-called dispersed generation, based on the local energy sources and the working systems utilizing both the fossil fuels and the renewable energy resources is observed nowadays. Generation of electricity on industrial or domestic scale together with production of heat can be obtained for example through employment of the ORC systems. It is mentioned in the EU directive 2012/27/EU for cogenerative production of heat and electricity. For such systems the crucial points a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Therefore, the crossflow role cannot be neglected in the case of the proposed solution of the heat exchangers. An theoretical and experimental analyses of the prototype constructions [27,28] revealed that the innovative idea of jet technology application facilitates in particular the heat transfer at low fluid flow rates and/or with a small temperature difference between fluids. This paper presents further research conducted on the intensification of heat transfer and reduction of the hydraulic resistance in a patented design of the minijet heat exchanger [24], for a future optimization of the construction.…”
Section: Minijets Heat Exchanger (Mjhe)mentioning
confidence: 99%
“…Therefore, the crossflow role cannot be neglected in the case of the proposed solution of the heat exchangers. An theoretical and experimental analyses of the prototype constructions [27,28] revealed that the innovative idea of jet technology application facilitates in particular the heat transfer at low fluid flow rates and/or with a small temperature difference between fluids. This paper presents further research conducted on the intensification of heat transfer and reduction of the hydraulic resistance in a patented design of the minijet heat exchanger [24], for a future optimization of the construction.…”
Section: Minijets Heat Exchanger (Mjhe)mentioning
confidence: 99%
“…In Table 3, locations of turbulence kinetic energy maxima are listed, in relation with orifice diameter D. They were established for flat and non-flat cases in the same manner, as data from Figure 8. Differences between each case existit is an important aspect to mention, because it may influence the results when the jets array impingement occurs, such as in [1][2][3]. Multiple jets might strongly interfere with each other.…”
Section: Flat Surface Validation Casementioning
confidence: 99%
“…It was being used in the cooling systems of electronics or in some metallurgical processes. Recently, however, it was proposed in the novel construction of cylindrical heat exchanger [1], which resulted in very promising values of transferred heat rates and lower than in other similar devices hydraulic resistance [2][3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations